Molecular detection of pore-forming leuko toxin in methicillin resistant Staphylococcus aureus isolated from skin infection - Sara A. Al-Ghazal; Huda H. Al-Hassnawi (Medical Journal of Babylon)
Abstract Background: The ability of Staphylococcus aureus to cause disease has been attributed to an impressive spectrum of virulence factors. Objective: The study investigated molecular detection of pore-forming leuko toxin (Panton–Valentine leucocidin [PVL]) in S. aureus that is resistant to methicillin (MRSA) isolated from skin infections. Materials and Methods: All 100 isolates of S. aureus were obtained from clinical samples (burn, wound, impetigo, boil, acne, abuses, folliculated, infected atopic dermatitis, and secondary infection), and 24 of these had been confirmed as MRSA. Antibiotic susceptibility patterns, mecA, 16sRNA, and PVL genes were isolated and detected by polymerase chain reaction (PCR). Results: All isolates were determined to be resistant to cefoxitin discs and oxacillin by using phenotypic analysis, and a genotypic investigation revealed that 79.16% of them carried the mecA gene. Additionally, the data showed that 58.33% of MRSA isolates contain the PVL gene and 83.33%% of MRSA isolates harbor of 16sRNA gene. Conclusions: The study detected a high S. aureus isolates percentage in a burn, followed by impetigo, wound, and boil, respectively. A higher percentage of MRSA isolates contain the PVL gene, mecA, and harbor of 16sRNA gene.